Analisis Kinerja Pegawai Pada Kantor Kelapa Lima - Jeujanan, Welhelmina; Oja, Hubertus; Moento, Paul Adryani; Saleky, Dandy (SOCIETAS, 2024)
Employee Performance Analysis is critical to achieving its goals. Higher performance means increased efficiency, effectiveness, or higher quality from completing tasks assigned to an employee in an organization or company. That is the importance of a system and procedure for implementing work, especially regarding management. The researcher uses qualitative methods with data analysis techniques, namely data reduction, data presentation, and conclusion drawing. This research is included in the type of qualitative research with a descriptive description of the number of informants in this research was 8 people. Based on the research results above, it can be concluded that the performance of Kelapa Lima sub-district employees in providing services to the community in Kelapa Lima sub-district is quite good because in providing servants to the community, the sub-district employees always try to serve well. Everything is going well according to the procedures implemented in Kelapa Lima sub-district, starting from productivity, accountability, behavior, and participation. However, there are still obstacles to performing services in implementing services. Some people do not understand the equipment requirements to take care of files, and some still do not understand computer mastery, which hinders employee performance in service to the community.